Production of clavulanic acid and cehphamycin C by Stretpmyces clavuligerus in palm oil medium - Lee, Ping Chin; C C Ho (Springer, 1996)
Palm and palm-kernel oils and their olein and stearin fractions were suitable as the main carbon sources for growth and production of clavulanic acid by Streptomyces clavuligerus. However, oleic and lauric acids were not utilized for growth. A spontaneous mutant, which was selected for higher cephamycin C production, also produced more clavulanic acid with these oils in the medium.